Smart steps in learning Arabic language Langkah-langkah bijak untuk belajar bahasa Arab - Qais Faryadi bin Sadrudeen
The lessons, exercises and test in this " Smart Steps In Learning Arabic Language" have been designed to help children learn the Arabic Language effectively and efficiently. The 10 lessons incorporate revision of previous lessons to enable the student to retain and review the old and new words to ensure systematic development of vocabulary. The test at the end of the 10 lessons help to evaluate the child's learning level.